Risk factors of conversion of laparoscopic totally extraperitoneal repair of inguinal hernia - Bhardwaj, Shreya; Krishnanand,; Samuel, Tanmay; Chaudhary, Shivam (International Surgery Journal, 2024)
Background: Inguinal hernia occurs in 1 to 5% of the general population. The development of laparoscopic inguinal hernia repair techniques as an alternative to conventional open surgery has improved results such as less postoperative pain, shorter hospital stays, and faster recovery. This study was conducted to assess the risk factors of conversion of laparoscopic totally extraperitoneal repair of inguinal hernia. Method: A total of 200 patients who were scheduled to undergo TEP were enrolled. Complete demographic and clinical details of all the patients was obtained. A Performa was made and detailed intraoperative findings were evaluated. Baseline hemodynamic and biochemical profile was evaluated. Separate assessment of patients was done who were converted to open surgery. Comparison of patients was done among those with and without conversion. Various risk factors were evaluated which were responsible for conversion. All the results were recorded in Microsoft excel sheet and were subjected to statistical analysis using SPSS software. Results: Mean age of the patients was 49.2 years. 60.5 percent of the patients were of rural residence. Mean BMI of the patients was 24.8 Kg/m2. Incidence of conversion was 6.5 percent. Geriatric age, obesity, higher ASA grade, larger hernial defects, larger peritoneal tear and previous hernia surgery history was found to be significant risk factors for conversion. Conclusion: Laparoscopic totally extraperitoneal (TEP) repair of inguinal hernia is an effective technique, but conversion to open surgery occurs in 6.5% of cases. Significant risk factors for conversion include geriatric age, obesity, higher ASA grade, larger hernial defects, larger peritoneal tear, and previous hernia surgery history. Identifying these risk factors can help optimize patient selection and improve outcomes for TEP repair.